Faktor-faktor yang Berperan dalam Meningkatkan Niat Beli Konsumen Produk Thrift Melalui TikTok Live Stream - Ja’farush Shiddiiq; Usep Suhud; Terrylina Arvinta Monoarfa (Digital Bisnis: Jurnal Publikasi Ilmu Manajemen dan E-Commerce, 2024)
This study aims to examine the effect of social media marketing, perceived quality, brand awareness, and brand image on purchase intention of thrift products through TikTok live stream. This research is a quantitative research. Primary data was collected by distributing questionnaires to 221 respondents aged 17-35 years who use the TikTok application and are interested in thrift products located in DKI Jakarta. Purposive sampling was chosen as the sampling method, so that samples were taken with certain conditions. These conditions include: 1) TikTok application users, 2) Domiciled in DKI Jakarta, 3) Aged 17-35 years, 4) Have seen Thrift Shop live streams/content on TikTok, 5) Intend to buy thrift products on TikTok. The results of primary data analysis were carried out using the Structural Equation Modeling (SEM) method. The scale measurement used by researchers is a Likert scale of 1-6. Outlined from Strongly Disagree, Disagree, Slightly Disagree, Slightly Agree, Agree, and Strongly Agree. The results showed that social media marketing has an influence on perceived quality, brand awareness, and brand image. Then, the results also show that perceived quality and brand image affect purchase intention. Furthermore, brand awareness does not have a significant influence on purchase intention.